Factors affecting Farmers’ Choices for Producing Organic Products in India: An Empirical Study - BHARDWAJ, RAJNEESH (International Journal of Psychosocial Rehabilitation, 2024)
The production of organic products has gained significant attention worldwide due to growing concerns over food safety and environmental sustainability. In India, where agriculture has a crucial part in the economy, there is a significant interest in organic farming. However, the implementation of organic farming practices by farmers is still limited and the factors that influence farmers' choices for producing organic products are not well understood. This empirical study aims to identify the factors affecting farmers' choices for producing organic products in India. Economic benefits, such as higher prices for organic products and lower input costs, are the main motivation for farmers to implement organic farming practices and it is also influenced by several other secondary factors such as access to information, availability of inputs, access to markets, and government policies. The study highlights the challenges faced by farmers in producing organic products and also concludes that promoting organic farming in India requires a multi-pronged approach that addresses the socio-economic, environmental, and policy-related factors that impact farmers' choices.